Analysis of Living Values in the Textbook of Civic Education in Higher Education - Usmi, Rianda; Jatiningsih, Oksiana; Kartika Sari, Maya Mustika (KnE Social Sciences, 2024)
The purpose of this research is to identify and examine the living values in 2016 civics textbooks produced by the Ministry of Technology, Research, and Higher Education. The technique used was content analysis. Reading, examining the contents of the book, and taking notes with meticulous examination of the substance of life values in the textbooks were used to gather data. The data were analyzed by examining the material content in each chapter. The results of the study show that the values of life contained in the teaching materials in civics education textbooks for college are unity, love, responsibility, tolerance, cooperation, freedom, peace, happiness, and honesty. The most dominant life values in the teaching materials in civics education textbooks for college are the values of unity and love. Nonetheless, in general, the material in the civics education textbooks for college which were made by the Directorate General of Learning and Student Affairs of the Ministry of Technology Research and Higher Education is still full of theoretical and conceptual or cognitive aspects, so it is still lacking in attitudes and behavior aspects. The development of basic values of life in teaching materials for civics education courses should be presented in the overall framework of learning materials in the form of facts, concepts, principles, and procedures which include an introduction, keywords, concept maps, discussion of the material, appreciation of values, conclusions, reflections, and references. Keywords: living values, textbooks, civic education, higher education